2019
DOI: 10.1016/j.jsps.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Career Choices and Preferences of Saudi Pharmacy Undergraduates: A Cross Sectional Study

Abstract: BackgroundDespite the increasing number of pharmacy schools and their graduates, the healthcare workforce shortage has increased in Saudi Arabia’s pharmacy sector, especially with the opening of new retail pharmacies, industries and pharmaceutical companies, which means that more pharmacist positions have been created with expanded working hours. However, very limited data are available regarding the views and preferences of pharmacy students regarding their future job choices in Saudi Arabia, which may create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
38
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 8 publications
15
38
4
Order By: Relevance
“…( Bin Saleh et al, 2015 ) This is also similar to findings from a study that took place in the United States where work environment was the most important job consideration for students when choosing a career. ( Savage et al, 2009 ) In contrast, Alhomoud et al (2019) , found that advancement in the profession, job openings in a certain field, and salary were the three most important factors that influence the students’ selection of future job. ( Alhomoud et al, 2019 ) In addition, a study by Savage et al (2009) , found that salary and advancement opportunities were the two least important job considerations on students’ career choices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…( Bin Saleh et al, 2015 ) This is also similar to findings from a study that took place in the United States where work environment was the most important job consideration for students when choosing a career. ( Savage et al, 2009 ) In contrast, Alhomoud et al (2019) , found that advancement in the profession, job openings in a certain field, and salary were the three most important factors that influence the students’ selection of future job. ( Alhomoud et al, 2019 ) In addition, a study by Savage et al (2009) , found that salary and advancement opportunities were the two least important job considerations on students’ career choices.…”
Section: Discussionmentioning
confidence: 99%
“…( Savage et al, 2009 ) In contrast, Alhomoud et al (2019) , found that advancement in the profession, job openings in a certain field, and salary were the three most important factors that influence the students’ selection of future job. ( Alhomoud et al, 2019 ) In addition, a study by Savage et al (2009) , found that salary and advancement opportunities were the two least important job considerations on students’ career choices. ( Savage et al, 2009 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…'Economic status' and 'Personal background' influence the career choices of both medical and pharmacy students (Lefevre et al, 2010;Alhomoud et al, 2019). Research has shown that people tend to adjust their behaviour and decision-making in an adaptive way, according to environmental circumstances, and decide on career choices that involve lower investment (Hill et al, 2008;Gigerenzer & Goldstein, 2011).…”
Section: Discussionmentioning
confidence: 99%